APPROACHES FOR BREACHING YIELD STAGNATION IN POTATO* - Pandey, S. K (Potato Journal, 2013)
India’s food security reached a threatening nadir during first half of 1960s when her population was increasing at an annual rate of about 2.2% but cereal production was virtually declining. Timely intervention of superior technologies and human endeavor avoided the inevitable famine and starvation, and virtually reversed the paradox of Malthusian model. Rice production more than doubled from 1961 to 1991, and wheat production almost quadrupled in that period bringing in green revolution in our country. Green revolution helped achieving food self-sufficiency, and subsequently, a growing stock of surplus food grains by the mid-1970s. However, yield gain in major cereals started leveling again by 1990s. Because of that, growth in agriculture sector faltered during 9th plan and is declining continuously during 10th plan. Yet the demand for cereals is expected to rise substantially in the next two decades. Because of this grim scenario, hon’ble prime minister of India urged the nation to enhance agricultural growth substantially during the 11th five year plan.